Phase transition approach to high temperature superconductivity : - Schneider, T. (Imperial College Press, 2000)
This book offers an understanding from the phase transition point of view, surveys and identifies thermal and quantum fluctuation effects, identifies material-independent universal properties and provides constraints for the microscopic description of the various phenomena. The text is presented in a format suitable for use in a graduate level course.